2007
DOI: 10.1248/cpb.55.853
|View full text |Cite
|
Sign up to set email alerts
|

Structures and DNA-Binding and Cleavage Properties of Ternary Copper(II) Complexes of Glycine with Phenanthroline, Bipyridine, and Bipyridylamine

Abstract: Recently, the interaction of Cu(II) complexes with nucleic acid has attracted attention due to the study of mutation of genes and therapeutic approaches, [2][3][4][5][6] because DNA is thought to be the target of the chemotherapy in the treatment of tumors.7) Some ternary complexes of Cu(II) of 1,10-phenanthroline(phen) have antitumor activity. 8) Various novel Cu(II) complexes with different ligand species have been designed and synthesized, 3,9) and the interaction of complexes with DNA has been characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…The high anti-proliferative activity of [phenH][VO(nta)(H 2 O)](H 2 O) 0.5 can be assigned to the intercalating properties of the phen derivative that interacts more strongly with DNA than the bpy derivative. A similar relationship in the reactivity towards DNA has also been found for other phen and bpy metal coordination compounds (Yodoshi et al 2007; Chakravarty 2006).
Fig.
…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The high anti-proliferative activity of [phenH][VO(nta)(H 2 O)](H 2 O) 0.5 can be assigned to the intercalating properties of the phen derivative that interacts more strongly with DNA than the bpy derivative. A similar relationship in the reactivity towards DNA has also been found for other phen and bpy metal coordination compounds (Yodoshi et al 2007; Chakravarty 2006).
Fig.
…”
Section: Resultssupporting
confidence: 76%
“…3) revealed that the DNA cleavages caused by VO(oda)(bpy) and VO(oda) were similar, while VO(oda)(phen) showed a stronger effect. VO(oda)(phen) presented the most potent antitumor action in human osteosarcoma cells followed by VO(oda)(bpy) and then by VO(oda) according to the number of intercalating heterocyclic moieties (Yodoshi et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…15,19) 0.76 mmol of bpy, phen or bpa were mixed with 0.76 mmol of PdCl 2 · 2NaCl · 3H 2 O in 5 ml of 80% (v/v) methanol-water solution for about 5 min at room temperature. The precipitates appeared after adding palladium salt.…”
Section: Methodsmentioning
confidence: 99%
“…Oxidovanadium(IV) complexes are the subject of interest to many research groups since it has been found that they reveal an interesting biological activity. Much attention has been focused on studies of their insulin‐mimetic (‐enhancing) properties, the anticancer properties as well as the cytoprotective activity against an oxidative damage . However, the main challenge in designing new oxidovanadium(IV) complexes for the future use in medicine is the selection of the appropriate type of ligands in order to overcome the balance existing between the therapeutic action and adverse effects exerted by vanadium compounds by shifting this balance toward the beneficial side.…”
Section: Introductionmentioning
confidence: 99%